Assembly Line Worker Assignment and Balancing Problem by Considering Labor Cost - Yılmaz, Hamid (Bursa Teknik Üniversitesi, 2022)
Assignment of worker appears as a new problem in the literature for assembly lines (AL) where the workforce is heterogeneously located. The difference of this line balancing from the traditional line is that the assembly task times of the workers to be assigned to the stations differ from each other. Especially assembly lines issues are generally a labor-intensive type of production. Therefore, for assembly line problems, balancing activity should be done considering the labor costs. Thus, the proposed solutions will be able to produce more realistic results for real life. For this purpose, in this study, a mixed-integer mathematical formulation is presented for assembly line worker assignment and balancing problems by considering the objective function of minimizing labor costs and cycle time. The efficiency of the proposed model and the improvements have been demonstrated by solving test instances in the literature.
Keywords: Engineering; Mühendislik